1977
DOI: 10.1128/iai.18.1.8-13.1977
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of live attenuated plague vaccines in Praomys (Mastomys) natalensis

Abstract: A live attenuated Yersinia pestis vaccine designated EV76-51f, which had previously been shown to be pathogenic in vervet monkeys but not in guinea pigs, was tested in the multimammate mouse Praomys (Mastomys) natalensis. Doses of 106 viable organisms inoculated subcutaneously as either a lyophilized suspension or an agar-grown culture resulted in vaccination fatalities in Praomys but not in white mice. Hemagglutinating antibodies to the fraction 1 antigen were not stimulated by doses lower than 104 viable org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This vaccine provides protection against bubonic plague, but there is good evidence that the vaccine provides little protection against primary pneumonic plague (9,27,37), and adverse side effects are known to occur (25,32). A live, attenuated vaccine with particular focus on the use of the EV76 pigmentationnegative Y. pestis strain has been developed; however, severe side effects have been observed (27,33), as have various levels of virulence among host species (8,16,28).…”
mentioning
confidence: 99%
“…This vaccine provides protection against bubonic plague, but there is good evidence that the vaccine provides little protection against primary pneumonic plague (9,27,37), and adverse side effects are known to occur (25,32). A live, attenuated vaccine with particular focus on the use of the EV76 pigmentationnegative Y. pestis strain has been developed; however, severe side effects have been observed (27,33), as have various levels of virulence among host species (8,16,28).…”
mentioning
confidence: 99%
“…As already noticed very early, Mastomys is highly susceptible to plague without any resistance to Yersinia pestis [57], which 1939 initially led to the breeding of Mastomys for plague research at the Medical Ecology Center in Johannesburg, South-Africa. In 1974, a plague outbreak in Zimbabwe (the former Rhodesia) [58] emerged with Mastomys as its primary reservoir host which were in turn used to test attenuated Y. pestis strains for vaccination [59]. Although previously suggested that there may be different sibling species of Mastomys [60], the discrimination between M. natalensis and M. coucha via chromosomal G-banding, was not successful before 1977 [61] and in 1983 it turned out that the latter is actually sensitive to Y. pestis [62,63].…”
Section: Mastomys As Model Systems In Biomedical Research—historicmentioning
confidence: 99%